SIMULTANEOUS SPECTROPHOTOMETRIC DETERMINATION OF TELMISARTAN AND HYDROCHLOROTHIAZIDE IN PHARMACEUTICAL PREPARATIONS BY RATIO SPECTRA DERIVATIVE METHOD - AKTAŞ, A. Hakan; SARI, Hülya (Universal Journal of Pharmaceutical Research, 2023)
Background: As it is known, antihypertensive drugs are frequently used for the treatment of individuals with high blood pressure all over the world. This study aims is to precisely determine the active substances of telmisartan and hydrochlorothiazide, which are commercially sold as high blood pressure drugs in the market, and to use the ratio spectrum method for this purpose. Method: All, solutions of the active ingredients of the drugs studied in the method were prepared in various concentrations. Subsequently, mixtures were prepared in accordance with the commercial drug sample, their spectra were taken by spectrophotometric method, and the spectrum ratio method was successfully applied to these data sets. Results: The study revealed that the application of the ratio spectra first-order derivative spectrophotometric method yielded highly reliable outcomes in the spectrophotometric analysis of different combinations of telmisartan and hydrochlorothiazide. Conclusion: The applied method can be used in the field of drug development. Peer Review History: Received: 10 February 2023; Revised: 16 March; Accepted: 23 April 2023, Available online: 15 May 2023 Academic Editor: Dr. Sally A. El-Zahaby , Pharos University in Alexandria, Egypt, sally.elzahaby@yahoo.com Reviewers: Prof. Cyprian Ogbonna ONYEJI, Obafemi Awolowo University, Ile-Ife, Nigeria, conyeji@oauife.edu.ng Dr. Wafa Mohamed Al Madhagi, Sana’a University, Yemen, walmadhaji1983@gmail.com